207 RE-DEFINING ARRHYTHMOGENIC CARDIOMYOPATHY: CHARACTERIZATION AND LONG-TERM PROGNOSTIC IMPLICATIONS. (15th December 2022) - Setti, Martina; Merlo, Marco; Gigli, Marta; Munaretto, Laura; Paldino, Alessia; Stolfo, Davide; Loco, Carola Pio; Medo, Kristen; Barbati, Giulia; Graw, Sharon; Ribichini, Flavio Luciano; Ferro, Matteo Dal; et al.
Abstract: Background: Arrhythmogenic dilated cardiomyopathy (AR-DCM) combines phenotypical aspects of dilated cardiomyopathy (DCM) and risk of sudden cardiac death (SCD), typical of the arrhythmogenic form (ACM). However, AR-DCM is often ambiguously defined leaving clinicians uncertain on how to identify these high-risk patients. The aims of the study were to re-define AR-DCM based on outcome related arrhythmic markers and to test the usefulness of the novel AR-DCM definition in identifying arrhythmogenic genotypes (i.e., LMNA, FLNC, RBM20, and desmosomal genes). Materials and methods: Consecutive DCM patients with genetic evaluation and Holter ECG monitoring or telemetry in two referral institution were analyzed. The arrhythmic markers tested to define AR-DCM were: SCD or major ventricular arrhythmias (MVA), unexplained syncope, rapid nonsustained ventricular tachycardia (nsTV), ≥1000 premature ventricular contractions/24 hours, or ≥50 ventricular couplets/24 hours. Patients were labeled as Early AR-DCM if criteria were met within 12 months from enrolment. The primary endpoint was a composite of SCD/MVA; the secondary endpoint was a composite of all-cause mortality/heart transplant/LVAD implantation (D/HTx/LVAD). Results: Among the 743 DCM patients included, 290 had disease-related variants (39%), 94 (30%) of these carried arrhythmogenic genotype. Early AR-DCM was identified in 429 (58%) patients. During a median follow-up of 7.0 [2.2-13.8] years, among arrhythmic markers the occurrence of syncope and/or nsVT within 12 months from enrolment were the only arrhythmic markers independently associated with SCD/MVA (Figure ), while the occurrence of early MVA and/or nsTV emerged as the strongest long-term predictors of D/ HTx/LVAD. Family history of MVA was also independently associated with primary and secondary endpoints, and together with MVA, nsTV or unexplained syncope increased the agreement between AR-DCM and arrhythmogenic genotypes in 1 out 2 patients. Conclusions: A combination of early (i.e., within 1 year from diagnosis) MVA or nsVT or unexplained syncope might be proposed as a clinically useful new definition of AR-DCM, especially if associated to family history of MVA. This definition in fact allows clinicians to anticipates worse long-term arrhythmic and global outcomes, and to accurately identify malignant arrhythmogenic genotypes.